Analisis Perbandingan Kinerja Bank Perkreditan Rakyat (BPR) Berdasarkan Metode CAMEL di Kabupaten Gorontalo - Onong Junus; Nurhayati Lagata (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
This study aims to determine and compare the performance level of PT. BPR Paro Dana and PT. BPR Asparaga Adiguna Bersama in Kabupaten Gorontalo during the period 2014-2015. By doing the soundness analysis of banks based on CAMEL method. Result of research indicate that PT. BPR Asparaga Adiguna Bersama has a level of performance that one level better if compared with PT. BPR Paro Dana. However, the second condition of BPR is still very far from the word healthy, which is not in accordance with the provisions stipulated by Bank Indonesia. Based on the results of the analysis, the hypothesis that PT. BPR Asparaga Adiguna Bersama has a healthy performance based on CAMEL theory compared to PT. Paro Dana, not received.